Endocrine effects of lifelong exposure to low-dose depleted uranium on testicular functions in adult rat. (10th August 2016) - Legendre, Audrey; Elie, Christelle; Ramambason, Camille; Manens, Line; Souidi, Maamar; Froment, Pascal; Tack, Karine
Abstract: Environmental toxicant exposure can induce disorders in sex steroidogenesis during fetal gonad development. Our previous study demonstrated that chronic adult exposure to a supra environmental concentration of depleted uranium (DU) does not impair testicular steroidogenesis in rats. In this study, we investigated the effects of lifelong exposure (embryo – adult) to low-dose DU (40 or 120 mg L −1 ) on adult rat testicular steroidogenesis and spermatogenesis. A significant content of uranium was detected in testis and epididymis in the DU 120 mg L −1 group and the assay in epididymal spermatozoa showed a significant content in both groups. No major defect was observed in testicular histology except a decrease in the number of basal vacuoles in the DU groups. Moreover, plasma Follicle-Stimuling Hormone [FSH] and Luteinizing Hormone [LH] levels were increased only in the DU 120 mg L −1 group and intratesticular estradiol was decreased in both groups. Testosterone level was reduced in plasma and testis in the DU 40 mg L −1 group. These modulations could be explained by an observed decrease in gene expression of luteinizing hormone receptor ( LHR ), and enzymes involved in steroid production and associated signal transduction ( StAR, cyp11a1, cyp17a1, 3βhsd, 17βhsd, TGFβ1, AR) . Several genes specific to germ cells and cell junctions of the blood-testis barrier were also modulated. In conclusion, these data show that fetal life is a critical window for chronic uranium exposure and that the endocrine activities of low-dose uranium could disrupt steroidogenesis through the hypothalamic-pituitary-testicular axis. Further investigation should be so useful in subsequent generations to improve risk assessment of uranium exposure.